2010
DOI: 10.1186/1471-2350-11-64
|View full text |Cite
|
Sign up to set email alerts
|

Custom CGH array profiling of copy number variations (CNVs) on chromosome 6p21.32 (HLA locus) in patients with venous malformations associated with multiple sclerosis

Abstract: BackgroundMultiple sclerosis (MS) is a complex disorder thought to result from an interaction between environmental and genetic predisposing factors which have not yet been characterised, although it is known to be associated with the HLA region on 6p21.32. Recently, a picture of chronic cerebrospinal venous insufficiency (CCSVI), consequent to stenosing venous malformation of the main extra-cranial outflow routes (VM), has been described in patients affected with MS, introducing an additional phenotype with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 38 publications
0
22
0
1
Order By: Relevance
“…These authors reported that CCSVI was associated of copy number variations in the HLA region for a small group of 15 MS patients [13]. In other diseases with venous pathophysiologies, a role for gender, and environmental and genetic factors is suggested.…”
Section: Discussionmentioning
confidence: 97%
“…These authors reported that CCSVI was associated of copy number variations in the HLA region for a small group of 15 MS patients [13]. In other diseases with venous pathophysiologies, a role for gender, and environmental and genetic factors is suggested.…”
Section: Discussionmentioning
confidence: 97%
“…It has been hypothesized that CCSVI might favourite erythrocytes diapedesis, and subsequent iron deposition [12,13,38,46]. Even though this is an intriguing and interesting hypothesis and a genetic dependence of CCSVI has recently been described by our group [47], other authors do not directly link CCSVI with increased iron and MS [48-50]. …”
Section: Discussionmentioning
confidence: 93%
“…The most important finding was that small IJV represents an independent factor associated with MS severity. It has been suggested that venous malformations may have a genetic etiology, and both environmental and genetic factors could play a role in venous pathophysiology [29,30]. Asymmetries and inborn anatomical differences have been observed in the truncular venous system [31,32], particularly during catheterization/interventional procedures in different groups of patients [11,33-36].…”
Section: Discussionmentioning
confidence: 99%